Korean Resident Registration System for Universal Health Coverage - Kang, Minah; Bae, Green; Kim, Heeun; Hong, Seung Yeon; Mills, Samuel (World Bank, Washington, DC, 2019)
This paper is a comprehensive case study on how the Korean civil registration and vital statistics (CRVS) system facilitates achievement of universal health coverage (UHC) in the Republic of Korea. The case study briefly summarizes the resident registration system - the main part of the Korea CRVS system - and the health care system in Korea; it provides an overview of UHC-related problems from the perspective of three major stakeholders: patients, providers, and government. It presents case studies illustrating how the Korean resident registration number (RRN) system facilitates implementation of UHC in Korea, including three main areas of health service provision (prevention, treatment and management, and health care data usage). It discusses key considerations for UHC implementation using RRNs, focusing on personal information protection and use of health care data in UHC implementation; and, it presents lessons learned and provides a conclusion of the study.